Implications of Case Resolution Mechanism Due to Press Coverage through Non-Litigation Channels - Putra, Moch Rachmat Prawira Yudha; Rahayuningsih, Toetik (PT. Riset Press International, 2024)
Today's news development in the media is very rapid, both traditional and electronic. Following technological developments, people can receive news from media worldwide directly through various means such as television, radio, newspapers, and even the Internet. Therefore, as a democratic country, Indonesia must be able to fulfill its obligation to guarantee press freedom and encourage the press to serve the interests of the public in seeking information. The national press appears increasingly free and unlimited in today's information technology era. For example, news considered harmful by a particular person or group can cause friction between the press and the public, giving rise to disputes over the behavior of press operators and news considered detrimental by certain groups. All disputes can be resolved through arbitration procedures stipulated in Law No. 40 of 1999 (from now on referred to as the Press Law) through mediation through non-judicial channels. However, not all disputes resolved in such a way can satisfy the parties and create legal certainty.